Facilitating community connections among people with mental illnesses: Perspectives from grassroots community leaders. Issue 3 (30th November 2018) - Bromage, Billy; Barrenger, Stacey L.; Clayton, Ashley; Rowe, Michael; Williamson, Bridgett; Benedict, Patricia; Kriegel, Liat S.
Abstract: We conducted focus groups comprising 20 grassroots community leaders to identify social and structural elements that affect community engagement among people with serious mental illnesses. Community leaders not affiliated with mental health systems have been mostly left out of the discussions about inclusion and engagement, even though they possess unique information about the places where they live and can be essential partners in making community connections. The findings from the focus groups point to elements that both facilitate and inhibit connections, as well as roles community mental health practitioners may take on, to engage with community leaders and people with mental illness to minimize barriers and foster connections in community settings. Additionally, the focus groups elucidated the interplay between the right to be a member of one's community and a community's responsibility to create a welcoming environment. The current study garnered information regarding the broader needs and implications of community connections, as well as some specific suggestions to enhance community engagement among people with serious mental illness. Hesitation and stigma around engaging individuals with mental illnesses were identified as barriers to inclusion. Further study about how community leaders and groups may be involved in facilitating meaningful community connections is recommended.